JOINING THE CALL TO INCORPORATE SUSTAINABILITY INTO THE CANADIAN SOCIAL WORK PROFESSION - Firang, David (Canadian Social Work Review / Revue canadienne de service social, 2020)
A global concern about how unsustainable use of global natural resources engenders environmental, social, and economic injustices for the world’s most vulnerable population has been well established in the literature. Although the profession of social work has a long-standing tradition of advocating for social and economic justice, issues of environmental sustainability have yet to be fully incorporated into social work education and practice. While the connection between the natural environment and social work education is robustly emerging in Australian and American literature, the Canadian social work literature is also paying attention to issues of environmental sustainability. In response to the 2018 call by the Canadian Association for Social Work Education – Association canadienne pour la formation en travail social (CASWE-ACFTS) (2018) to revitalize efforts towards environmental sustainability in Canadian social work education, this article joins other Canadian social work educators to advocate for the profession to incorporate a novel global paradigm—sustainability—into social work practice. Drawing on relevant literature and other empirical studies, this article aims to increase our understanding of the critical impact of a lack of sustainability on Canada’s poorest, most vulnerable, and oppressed people (such as Indigenous Peoples), who often live in the most degraded environments and have no control over their own natural resources. I argue that incorporating sustainability into Canadian social work education and practice is achievable only if the professional bodies, namely the Canadian Association of Social Workers (CASW) and CASWE-ACFTS, provide institutional support by setting accreditation standards and ethical guidelines to reinforce sustainability in Canadian social work practice.